Automotive fundamentals fundamentals of engine operation (New Jersey : A Shopware Production, 2004)
This CD-ROM explains the internal combustion process and the four-stroke cycle in detail. each major component of the engine is clearly identified and its operation described, as well as the support systems of the engine, the oil system and the cooling system.
System requirements: 200 MHz processor, 32 MB RAM (64MB preferred), 4 x cd-rom drive, 800 x 600 display with 256 colors, soundcard and speakers or headphones, keyboard, mouse, QUICKTIME 4 or higher, Adobe Acrobat Reader.
Keywords: Automobiles; Motor vehicles; Mechanical engineering